Defective activation of neutrophils after splenectomy. Issue 10 (October 1985) - Foster, P N; Bolton, R P; Cotter, K L; Losowsky, M S
Abstract : Neutrophil chemotaxis and phagocytosis in the presence of serum from 20 patients who had undergone splenectomy and from 15 healthy volunteers was studied. The mean distance migrated by normal neutrophils in the presence of serum from the patients after splenectomy was significantly less than that when normal serum was used (p less than 0.005). The percentage of neutrophils phagocytosing a yeast was also significantly reduced in the presence of serum from patients after splenectomy (p less than 0.02). In addition, when neutrophils from these patients were studied both chemotaxis and phagocytosis were enhanced in normal compared with autologous serum (p less than 0.05).